﻿A new species of Gammarus (Crustacea, Amphipoda, Gammaridae) from South Korea - Yong-Uk Ahn; Chi-Woo Lee; Gi-Sik Min (ZooKeys, 2022)
A new species of freshwater gammarid, Gammarus somaemulensis sp. nov., was collected from Somaemuldo Island, South Korea. This new species is morphologically characterised by the absence of calceoli in antenna 2, absence of anteroproximal setae on bases in pereopods 6 and 7, outer ramus in uropod 3 with plumose setae on both margins, and a small terminal article of the outer ramus, which is shorter than adjacent spines. A description of the new species and morphological differences from related species are provided in the text. The new species was also compared to related species using partial sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Genetic distances of COI sequences between the new species and related species, consisting of 21.5–26.3% difference, support Gammarus somaemulensis sp. nov. as a valid species. Additionally, a key to identifying Gammarus species in South Korea is provided.